EFL LEARNERS’ GRAMMATICAL DEVIATIONS FROM CONCORD: What degree did they become mistakes and errors? - Isyam, Amri (English Department FBS UNP, 2010)
This article, based on the other part of the research entitled EFL Learners’ Concord Mastery and their grammatical Deviations carried out by the writer, aims at describing to what degree EFL learners have committed grammatical deviations from 3 types of concord: subject-verb concord (SVC), subject-complement concord (SCC), and subject-object concord (SOC) and to what extent those deviations became mistakes and errors. With the population of 120 EFL learners of three classes of the third year students of the English Department of the Faculty of Languages, Literature, and Arts of the State University of Padang, and with one class of them chosen as the sample comprising of 32 subjects by cluster-sampling technique, the data were gathered through a fifty-item test with one administration but with 4 versions of the answers. Thus, with 4 versions of grammatical deviations (GD): GD of version 1 (GD1), GD2, GD3, and GD4 taken from the answers of the test of version 1, 2, 3, and 4 respectively, and the overall grammatical deviations (OGD) as the accumulation of the 4 versions of GD, and by using quantitatively descriptive method, it was found out that on the average the EFL learners’ GD1 was more than one-third of the total test items (TTI), and that of the OGD was nearly a half of TTI. Besides, after the split of OGD into mistakes and errors it was known the ratio between the two kinds of GD was about 2:5, or in every 7 GD there were 2 mistakes and 5 errors on the average. Furthermore, there were 3 types of grammatical errors (GE) found for each kind of concord: omission, addition, and misformation. Misformation had the greatest percentages of GE for SVC and SOC. Most of the GE of this type dealt with the use of plural verbs for singular ones, that of possessive adjective (their) for reflexive genitive (their own), that of reciprocal pronoun referring to 2 peeople (each other) for reciprocal pronoun referring to 3 people or more (one another) and that of object pronoun (them) for reciprocal pronoun referring to 3 people or more (one another). For SCC the omission type of the GE had the greatest, and most of them were absence of plural indicators –s/-es.